2019
DOI: 10.32098/mltj.01.2019.13
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric study of the popliteus myotendinous complex with its clinical aspects

Abstract: Background. The aim of the present study is to study the morphometry of the muscle-tendon complex of popliteus, and to define a relatively safe zone in posterior approach to knee or popliteal region with respect to the bony landmarks for tibial nerve and nerve to popliteus. Method. 20 cadaveric legs were used for dissection. The attachments of popliteus, length and width of tendon as well as muscle belly, were defined and noted. An imaginary line extending from the medial to lateral epicondyles of femur was ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This is very important as it stabilizes the posterolateral aspect of the femoro-tibial articulation. According to Vani and Raveendranath, 9 the length and width of tendon of popliteus was 35.12 mm and 9.52 mm, which was comparable to the dimensions by Jung et al 10 and Osti et al 11 LaPrade et al 12 reported that the length of popliteus tendon measures 54.5 mm. In our research, the same parameters were 24.85 AE 2.15 mm and the width at the musculotendinous junction was 8.5AE1.15 mm.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This is very important as it stabilizes the posterolateral aspect of the femoro-tibial articulation. According to Vani and Raveendranath, 9 the length and width of tendon of popliteus was 35.12 mm and 9.52 mm, which was comparable to the dimensions by Jung et al 10 and Osti et al 11 LaPrade et al 12 reported that the length of popliteus tendon measures 54.5 mm. In our research, the same parameters were 24.85 AE 2.15 mm and the width at the musculotendinous junction was 8.5AE1.15 mm.…”
Section: Discussionsupporting
confidence: 71%
“…This was almost parallel to the findings of Vani and Raveendranath. 9 In the present study, this dimension was not performed and the morphometric data of the length and width of popliteus is different in our study in comparison to previous studies, as the different points were used for the measurements. The positive outcome of this anatomical research was we measured the length of the popliteus at both the upper and lower borders.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation